Eksistensi Qanun Nomor 9 Tahun 2008 Dalam Penyelesaian Tindak Pidana Penganiayan Ringan Di Kota Langsa - wahyu ramadhani (IAIN Langsa, 2020)
The existence of the village as an MHA (customary villagers), is in accordance with Article 18B paragraph (2) of the 1945 Constitution. The problem is, what are the traditional rights of indigenous peoples in the empirical level of customary law, effectiveness of conduct, Qanun Number 9 of 2008 in the process of applying and implementing qanun No. 9 of 2008 in the Langsa City District area, in resolving adat cases was clearly deemed ineffective. Where in its application Qanun No. 9 of 2008 has not provided the maximum contribution in solving various problems in the Langsa City community, especially with regard to adat criminal cases. There are a number of customary criminal cases that have been resolved but have not yet given maximum contribution to the settlement. The discussion method that I will use in this study is a qualitative method. Qualitative Method is the study of various studies and collections of various types of empirical material, such as case studies, personal experiences, introspective recognition, life stories, interviews, artifacts, various texts and cultural productions, observations, history, interactional, and various visual texts. Various empirical study materials are presented in the details of the problem at various moments and various meanings and various individual lives of descriptive analysis methods. The results of the study found that, First: The pattern of the application of the fostering of customary life and customs in resolving customary criminal cases in the District of Kota Sigli has not necessarily guided by the Qanun, so it has not yet made a maximum contribution. Second: The effectiveness of the effectiveness of Qanun Number 9 Year 2008 in resolving customary criminal cases in Langsa City District can be seen from the size of the process and the verdict is not effective. In conclusion, the customary court in resolving a case must always be guided by Qanun Number 9 of 2008 in order to obtain a legal provision so as to make the community live in comfort.